Stimulus-responsive nanopreparations for tumor targeting - Zhu, Lin (2013)
Nanopreparations such as liposomes, micelles, polymeric and inorganic nanoparticles, and small molecule/nucleic acid/protein conjugates have demonstrated various advantages versus “naked” therapeutic molecules. These nanopreparations can be further engineered with functional moieties to improve their performance in terms of circulation longevity, targetability, enhanced intracellular penetration; carrier-mediated enhanced visualization, and stimuli-sensitivity. The idea of application of a stimulus-sensitive drug or imaging agent delivery system for tumor targeting is based on the fact of the significant abnormalities in the tumor microenvironment and its cells, such as an acidic pH, altered redox potential, up-regulated proteins and hyperthermia. These internal conditions as well as external stimuli such as magnetic field, ultrasound and light, can be used to modify the behavior of the nanopreparations that control drug release, improve drug internalization, control the intracellular drug fate and even allow for certain physical interactions, resulting in an enhanced tumor targeting and antitumor effect. This article provides a critical view of current stimulus-sensitive drug delivery strategies and possible future directions in tumor targeting with primary focus on the combined use of stimulus-sensitivity with other strategies in the same nanopreparation, including multifunctional nanopreparations and theranostics.